TROPICAL EOCENE PALYNOMORPHS FROM THE TORAJA FORMATION, KALUMPANG, SOUTH SULAWESI - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2003)
This study enables to prove the occurrence of the tropical Eocene palynomorphs within the South Sulawesi area.